Update in research and methods in proteomics and bioinformatics. (October 2013) - Bencharit, Sompop; Border, Michael B; Edelmann, Alex; Byrd, Warren C
The 3rd International Conference on Proteomics & Bioinformatics (Proteomics 2013) Philadelphia, PA, USA, 15–17 July 2013 The Third International Conference on Proteomics & Bioinformatics (Proteomics 2013) was sponsored by the OMICS group and was organized in order to strengthen the future of proteomics science by bringing together professionals, researchers and scholars from leading universities across the globe. The main topics of this conference included the integration of novel platforms in data analysis, the use of a systems biology approach, different novel mass spectrometry platforms and biomarker discovery methods. The conference was divided into proteomic methods and research interests. Among these two categories, interactions between methods in proteomics and bioinformatics, as well as other research methodologies, were discussed. Exceptional topics from the keynote forum, oral presentations and the poster session have been highlighted. The topics range from new techniques for analyzing proteomics data, to new models designed to help better understand genetic variations to the differences in the salivary proteomes of HIV-infected patients.